Peran Dewan Keamanan dalam Mewujudkan Perdamaian dan Keamanan Internasional (Studi Kasus Perang di Bekas Wilayah Yugoslavia) - sefriani sefriani (Fakultas Hukum Universitas Islam Indonesia, 2000)
This article attempts to describe several roles of the Security Council of the United Nations in keeping international peace and security as its main duty. In addition, what obstacles for the board in implementing its duty and how its development recently is, will be discussed in the article. Moreover, this writing tries to review the cases of law enforcement conducted by the Security Council in the Bosnia Herzegovina war as the actual topic to look over